Data Intelligence Training for Library Staff - Madeleine de Smaele; Ellen Verbakel; Nicole Potters; Marina Noordegraaf (International Journal of Digital Curation, 2013)
The Data Intelligence 4 Librarians course was developed by 3TU.Datacentrum at the end of 2011 to provide online resources and training for digital preservation practitioners, specifically for library staff. The course objectives are to transfer and exchange knowledge about data management, and to provide participants with the skills required to advise researchers or research groups on efficient and effective ways of adding value to their data. The paper describes the process of creating the course, the methodology and the results of the first pilot, which took place from February to June 2012. It also demonstrates the choices made during the design process and discusses the implications of the evaluation of the pilot course for further development: in particular, how the course might be expanded to more disciplines and other data repositories.